Religious Literacy in Policy and Practice - Francis, Matthew (Matthew D. M.), 1975-; Dinham, Adam (Book collections on Project MUSE., 2015)
Often assumed to be in decline in the West, religion continues to have an important yet contested role in individual lives and in society. And after half a century in which religion and belief were barely talked about publicly, we face a pressing lack of religious literacy. Many are now ill-equipped to engage with religion and belief when they encounter them in their daily lives. This book brings together theory and policy with analysis and expertise to explore what religious literacy is, why it is needed, and what might be done about it.